(untitled) (Cultura Económica, 2019)
This article is an attempt to reinterpret “The Ethics of the Management Paradox” as it is formulated by the Leuven philosopher-economist Luk Bouckaert (2006) who analyses how to make business ethics operational and how to make business genuinely ethical. The question becomes to what extent ethical behavior constituting a good reputation can be “used” by corporate managers to enhance corporate value. In line with Bouckaert’s paradox, Peter Verhezen argues that instrumentalizing reputation would possibly undermine its objectives to achieve useful benefits.